Reciprocal Teaching Technique to Improve Students' Reading Comprehension (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
The purpose of this research was to find out significant difference in students' reading comprehension those taught using and without using reciprocal teaching technique. This research was experiment research. The participants of the research were tenth graders of SMAN 1 Godong in the academic year 2020/2021 which consisted of 30 students for control group and 30 students for experiment group. The instruments used to collect the data were from test. This research was conducted using quantitative methods in processing the data and getting the results. The design used was quasi-experimental, which involved two groups of students, namely the experimental group and the control group. The experimental group as the group that received treatment and the control group that did not receive treatment. Research result from SPSS showed the significance value is 0.02 or less than 0.05. This means the reading comprehension skills of students studied using reciprocal teaching technique differed with students who studied using reciprocal teaching technique. To sum up, the implementation of reciprocal teaching technique was able to provide positive results on their reading comprehension. The students felt enthusiastic and enjoy the lesson after being taught through reciprocal teaching technique. Therefore, the students' reading comprehension skills are significantly improved after being taught using reciprocal teaching technique. This can be concluded that reciprocal teaching technique approach has been shows to be effective in improving students' reading comprehension skills.
Keywords: reading comprehension, reciprocal teaching, reading strategies, metacognitive strategies